Inovasi Kewirausahaan Masjid Jogokariyan Sebagai Model Pemberdayaan Ekonomi Umat Di Era Disruptif - baharudin ardani; Cecep Catrawijaya (GLOBAL SCIENTS PUBLISHER, 2026)
Mosques historically serve as crucial centers for social and economic empowerment of the community (Ummah). However, the majority of Islamic philanthropic assets, particularly waqf (endowment), remain passive and fail to contribute optimally to economic development, especially when confronted with the rapid socio-technological changes characterizing the Disruptive Era. This study analyzes the entrepreneurial innovation model implemented by Jogokariyan Mosque in Yogyakarta as a structural solution for sustainable Ummah economic empowerment. The study’s objectives are to identify (1) the mosque’s productive waqf-based entrepreneurial innovation model, (2) institutional adaptation strategies during disruption, and (3) the model's impact on economic empowerment. A qualitative case study approach is employed, analyzing credible academic literature on mosque management and social entrepreneurship practices. Key findings reveal that Jogokariyan Mosque successfully implements an Islamic Social Entrepreneurship model sustained by diverse productive waqf assets (including Syariah Hotels, Agricultural Land, and a Bakery), thereby achieving institutional financial independence. Core innovations include revolutionary philanthropy governance (the Zero Balance Program) and disruptive adaptation strategies, such as the utilization of digital platforms and the marketing mix for incubating local Micro, Small, and Medium Enterprises (MSMEs) through the Jogokariyan People's Market (PRJ). This integrated model has successfully expanded job opportunities and increased the income of the local community. This research contributes a framework for a professional, accountable, and innovative institutional model that is replicable for the economic revitalization of mosques in a dynamically disruptive global context